Practice of the use of oral mucosa graft urethroplasty among Nigerian urologists - Agwu, Ngwobia P.; Umar, Ahmed M. (International Surgery Journal, 2020)
Background: Urethral stricture is an ancient disease that has plagued men. Management of this disease has been evolving due to advances in technology and better understanding of the pathogenesis. Use of oral mucosal grafts for substitution urethroplasty has been gaining world-wide acceptance and application by urologists. This article examines the of application of this urethral substitute among Nigerian urologists. Methods: This was a questionnaire-based study administered to urologists during the annual general meeting and scientific conference. Results: Forty two respondents completed the questionnaire and comprised of 41 (97.6%) males and 1 (2.4%) female. There were 24 (57.1%) consultants, senior registrars and others 4 (9.6%). Thirty three (78.6%) of the respondents had practised for less than 10 years. Region of practice in Nigeria were 13 (31%) in South-west, 5 (11.9%) in South-East, 3 (7.1%) in South -South, 9 (21.4%) in North-West, 10 (23.8%) in North-central and 2 (4.8%) in North-East. Annual volume of urethroplasty was less than 10 in 19 (45.2%) and only 3 (7.1%) performed more than 30 urethroplasties. Place of practice was mainly in the University Teaching Hospital 33 (78.6%). Oral mucosa grafts (OMGs) used either alone or in combination with penile flaps was used by 30 (71.4%) respondents while 11 (26.2%) used only penile skin flaps. Up to 10 (23.8%) of the respondents indicated desire to undergo training on the use of OMG for urethral reconstruction. Conclusions: Use of OMG is accepted by Nigerian urologists, however application is limited by low annual urethroplasty volume and lack of training.